Generation of 3-hr Long-Crested Waves of Extreme Sea States With HOS-NWT Solver - Canard, Maxime; Ducrozet, Guillaume; Bouscasse, Benjamin (Volume 6B: Ocean Engineering, 2020)
International audience The accurate control of wave fields generated in experiments and numerical simulations is of great interest for the ocean engineering community. In the context of wave-structure interactions, the recommended practices of classification societies are indeed based on the definition of a wave spectrum, that needs to be reproduced. The present work intends to address this problem from the numerical point of view, using a Numerical Wave Tank equipped with a wavemaker and an absorbing beach, based on the High-Order Spectral method (HOS-NWT). The challenging case of the generation of 3-hours long-crested extreme sea states is studied in details. An iterative procedure to reproduce a target wave spectrum at a given distance from the wavemaker is proposed. The quality of the sea state obtained is evaluated using several criteria defined from spectral quantities. A validation is first performed with a highly nonlinear but non-breaking sea-state. Statistical crest distributions obtained are compared with the Forristall and Huang distributions [1,2]. Then, the Gulf of Mexico 1,000 Year Return Period wave condition is generated. This corresponds to an extreme sea state with significant wave breaking occurrence. The numerical solver needs to be able to account for this phenomenon [3]. The Tian breaking model [4, 5] is calibrated to realistically reproduce the dissipation due to breaking, with particular attention paid to the spatial discretization, enlightening its significant effect on breaking model actions. Consequences on the iterative correction process are studied. The computed statistical quantities appear to be significantly different changing the spatial discretization, while the wave energy spectrum stands the same. It questions the relevance of the characterization of a sea state with the sole wave energy spectrum.